KAPASITAS KELEMBAGAAN DAN KEARIFAN LOKAL DALAM ANTISIPASI PENANGGULANGAN BENCANA MERAPI TAHUN 2010 DI KABUPATEN KLATEN (STUDI KASUS DI DESA BALERANTE KECAMATAN KEMALANG) - Galih Marendra; Edi Santosa; Nunik Retno H (Journal of Politic and Government Studies, 2014)
This research was motivated by the frequent occurrence of naturaldisasters occurring in Indonesia, especially the eruption of a volcano disasterMerapi in Klaten region which occurred in 2010. Here, we can see readiness ofLocal Government to face merapi disaster, considering the Merapi disaster occursevery few years. How government can coordinate every institution that relating todisaster management, infrastructure readiness for evacuation of disaster victimsuntil the budget allocated for disaster management. Experience from previousdisasters and local wisdom can be a lesson in facing disasters that happened. Thepurpose of this research is to determine the institutional capacity and the potentialof local wisdom in anticipation overcome of Merapi disaster in 2010 and thebarriers that faced. Through people local wisdom to face disaster and gooddisaster management application from the government could minimize the impactof Mount Merapi eruption disaster, particularly in the district of Klaten.Key word: Institutional, Local Wisdom, Disaster Management.